2022
DOI: 10.3389/fnins.2022.1059639
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying masking release by voice-gender differences and spatial separation cues in multi-talker listening environments in listeners with and without hearing loss

Abstract: Voice-gender differences and spatial separation are important cues for auditory object segregation. The goal of this study was to investigate the relationship of voice-gender difference benefit to the breadth of binaural pitch fusion, the perceptual integration of dichotic stimuli that evoke different pitches across ears, and the relationship of spatial separation benefit to localization acuity, the ability to identify the direction of a sound source. Twelve bilateral hearing aid (HA) users (age from 30 to 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
3
0
1
Order By: Relevance
“…It should be noted that the term “gender” denotes the classical categorization of a talker’s voice with their assigned sex at birth. In this study, we will refer to these benefits from talker sex differences as voice gender release from masking (VGRM), as referred to in the previous studies ( Oh et al, 2021 , 2022 ). Brungart and his colleagues reported the importance of voice characteristics in speech segregation in multi-talker listening situations ( Brungart et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the term “gender” denotes the classical categorization of a talker’s voice with their assigned sex at birth. In this study, we will refer to these benefits from talker sex differences as voice gender release from masking (VGRM), as referred to in the previous studies ( Oh et al, 2021 , 2022 ). Brungart and his colleagues reported the importance of voice characteristics in speech segregation in multi-talker listening situations ( Brungart et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of voice characteristic differences and spatial separation between talkers has been explored in previous studies ( Ericson et al, 2004 ; Allen et al, 2008 ; Oh et al, 2021 , 2022 ). First, Ericson et al (2004) reported that the speech-on-speech masking performance improved by 25% to 35% when same-sex competing talkers were separated spatially by ±45°, and the improvement is roughly equivalent to replacing the same-sex interfering talkers with different-sex interfering talkers (~102-Hz F0 differences).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…변동 소음이 배경소음으로 제시된 경우 변동 비율, 깊이, 유 형, 소음의 대역폭 및 강도 등과 같은 특성들이 청자의 FMB에 영향을 준다 (Festen & Plomp, 1990;Fogerty et al, 2016;Fogerty et al, 2018;Wagener et al, 2006). 난청인의 경 우 건청인에 비해 비교적 적은 FMB를 보이거나 FMB가 아 예 관찰되지 않기도 하였는데 (Eisenberg et al, 1995;Hall et al, 2012;Jensen & Bernstein, 2019;Wagener et al, 2006), 난청인의 청력 상태 혹은 역치상 시간해상 능력 (Dubno et al, 2003;Festen & Plomp, 1990;George et al, 2006;Summers & Molis, 2004;Takahashi & Bacon, 1992) (Hawley et al, 2004;Kidd et al, 1998;Marrone et al, 2008, Oh et al, 2022Yost, 2017). (Brennan et al, 2016;Hall et al, 2012).…”
Section: Introductionunclassified